DJERFISHERITE IN UNALTERED KIMBERLITES OF THE UDACHNAYA-EAST PIPE, YAKUTIA - Sharygin V.V.; Golovin A.V.; Pokhilenko N.P.; Sobolev N.V. (My University, 2003)
Djerfisherite K6Na(Fe,Ni,Cu)24S26Cl, first discovered in meteorites [1], was subsequently found in Cu–Ni ores, kimberlites, alkaline ultrabasic rocks and car-bonatites, peralkaline rocks, and in skarns around alka-line rock massifs. Clarke et al. [2] presented a review on findings of djerfisherite and its genesis. New relevant information was discussed in [3–5]. Djerfisherite is rare in kimberlites. This mineral was first identified in diamonds and xenoliths from kimberlites of Yakutia and South Africa as a phase that rims the primary Fe–Ni–Cu sulfides [6–8]. Subsequently, djerfisherite was detected in the groundmass of Canadian kimberlites from the Northwest Territories as a primary phase crystallized at the late magmatic stage [2, 9]. In this communication, we report the results of a comprehensive examination of djerfisherite from the groundmass of unaltered kimberlite breccia and the monticellite kimberlite of the Udachnaya-East pipe. Previously we had only detected and analyzed djerfisherite from secondary melt inclusions in olivine of kimberlite breccia [10].